Teacher Effectiveness in Relation to Self-Confidence and Students’ Academic Achievement in Secondary Schools - Saji Lukose; Dr. Agnes Humtsoe (Revista Electronica de Veterinaria, 2024)
This study aimed to investigate the relationship between teacher effectiveness, self-confidence, and student academic achievement in Karbi Anglong District, Assam. A survey method was used to collect data from a sample of 400 randomly selected secondary school teachers. The Teachers’ Effectiveness Scale developed by Shallu Puri and S. C. Gakhar in the year 2010 and Self-Confidence Scale developed by Babita Gupta and Avdhesh Jha in 2014 were used to gather information. The findings revealed that a significant majority of teachers (98.5%) exhibited a very low level of effectiveness and (1.5%) of teachers shown a low level of teacher effectiveness. A positive correlation was found between teacher effectiveness and self-confidence, suggesting that teachers with higher self-confidence tend to be more effective. However, no significant correlation was found between teacher effectiveness and student academic achievement. The study recommends strategies to enhance teacher effectiveness, including motivation, training, recognition, and a positive work environment. By implementing these strategies, schools can improve the quality of education and ultimately benefit student learning outcomes.